Developing an Environmental and Social Performance Index for Indonesian State-Owned Enterprises (ESPISOE): A GRI-Based Approach - Nagu, Nadhirah; Fauzi, Hasan; Yusoff, Haslinda (Journal of Posthumanism, 2025)
Indonesian state-owned enterprises (ISOEs) must meet environmental and social responsibilities under Laws No. 19/2003 and No. 40/2007, facing labor and environmental violations, social conflicts, and noncompliance. This study develops an Environmental and Social Performance Index (ESPISOE) based on Global Reporting Initiative standards to assess performance. The index integrates environmental, social, and governance practices into ISOEs, benefiting SOEs and stakeholders including employees, customers, suppliers, and native groups. ESPISOE was developed using data from 2008 to 2018. The top five ESPISOE rankings are: Timah (TINS) 2.856, Tambang Batubara Bukit Asam (PTBA) 2.480, Semen Indonesia (SI) 2.380, Aneka Tambang (ANTM) 1.185, and Perusahaan Gas Negara (PGAS) 1.085. Few studies examine SOE compliance with Law 19/2003 and normative accountability, mainly focusing on social and environmental performance. This study addresses non-compliance with employment and environmental laws, social conflicts, and policy deviations. The ESPISOE measures environmental and social performance of ISOEs.